DETEKSI GEN KETAHANAN HAWAR DAUN BAKTERI PADA PADI FAMILI F7 PERSILANGAN SINTANUR X PTB33 DAN FAMILI F5 PANDANWANGI X PTB33 SEBAGAI UPAYA AWAL SKRINING GENOTIPE POTENSIAL - Prayitno, Prayitno; Carsono, Nono; Anas, Anas; Mahardhika, Dimas Kembara (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The decrease in rice production due to bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) has been reported to be quite high, ranging from 15–23%. Based on its spread and rice losses due to this pathogen, efforts are highly needed to reduce and control it. The BLB resistance gene is called the Xa gene. Currently, there are 42 Xa genes controlling BLB resistance that have been identified in some cultivars, mutant population and wild species of rice. The Xa3, Xa4 and xa8 genes are the three well-known of bacterial leaf blight resistance genes in hybrid rice in China and South Asian countries. Considering their dominant existence in Indonesia, molecular screening by means of PCR detection has been done in eight families of F7 Sintanur x PTB33 and two families of F5 Pandanwangi x PTB33 for these three Xa genes. Molecular markers BB3RF, BB3RR, MP1, MP2, and RM21044 were applied to detect those three genes. Based on DNA visualization it was found that SP101-3-1-5-8, SP101-3-1-19-26, SP101-3-1-38-4, SP87-1-1-7-7, PP48-5-1, and PP48-5-24 had the Xa3 gene. The genotypes that carry the Xa4 gene were SP101-3-1-19-27, SP101-3-1-38-4 and SP101-3-1-38-25. Meanwhile, the xa8 gene was only detected in Pandanwangi, meanwhile the SP101-3-1-38-4 carried the Xa3 and Xa4 genes. No genotypes were found with three genes. The selected genotypes will be further developed in order to assembly multiple resistance genes for this particular disease.